2015
DOI: 10.1097/nmd.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Therapist Emotional Responses

Abstract: The aims of this study were to identify (a) patterns of clinicians' emotional responses to patients with eating disorders (ED); (b) patient, clinician, and treatment variables associated with therapist emotional responses; and (c) the influence of patient personality on therapist emotional responses. A random national sample of psychodynamic and cognitive-behavioral psychotherapists (N = 149) was asked to examine one patient (>18 years old) with an ED. Clinicians completed the SWAP-200, the Therapist Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…All participants found their work professionally rewarding. This is consistent with previous research that has also found high levels of professional satisfaction in individuals working in eating disorder services (Colli et al ., ; Davey et al ., ; Warren et al ., , ). However, participants identified specific challenges related to working with individuals with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants found their work professionally rewarding. This is consistent with previous research that has also found high levels of professional satisfaction in individuals working in eating disorder services (Colli et al ., ; Davey et al ., ; Warren et al ., , ). However, participants identified specific challenges related to working with individuals with eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Working with individuals with eating disorders also presents unique challenges. The treatment-resistant nature of eating disorders, client ambivalence, high rates of relapse and complex interpersonal relationships have all been identified as stressors related to working with individuals with eating disorders (Colli et al, 2015;Davey et al, 2014;Warren, Schafer, Crowley & Olivardia, 2012;Warren et al, 2013). Additionally therapists' emotional reactions to clients (referred to as 'countertransference'), particularly in response to perceived 'egocentric' personality traits, 'splitting behaviours' and other challenging behaviours, are often strong, challenging to manage and can lead to emotional exhaustion (Colli et al; Davey et al; Warren et al).…”
Section: Introductionmentioning
confidence: 99%
“…They also described a high level of anxiety and uncertainty concerning their assessments, and they elaborated on the consequences of potential premature termination of treatment. Empirical research suggests that therapists tend to develop more feelings of frustration, hopelessness, and helplessness in therapy with AN patients than with patients with other eating disorders [49]. However, existing studies tend to focus on patients' characteristics when addressing dropout from treatment and fail to include systemic or therapist factors, implying that the high dropout rates are primarily the patients' responsibility [36,50].…”
Section: Being Unprepared and Alone In The Transition Processmentioning
confidence: 99%
“…Countertransference has been studied thru various methods and designs, typically in case studies, in interviews, using external observer’s or supervisor’s assessment of therapist countertransference behavior, or in therapist self-report questionnaires (Colli & Ferri, 2015 ; Hayes et al, 2011 ). By using self-report instruments and factor analysis, a number of different categories of countertransference manifestations have been identified, mainly based on the totalistic definition of countertransference as the integrative approach to countertransference is difficult to access with self-report measures.…”
Section: Introductionmentioning
confidence: 99%
“…The TRQ has also been used to map different therapist reactions to patients’ personality disorder (Betan et al, 2005 ; Colli, Tanzilli, Dimaggio, & Lingiardi, 2014 ; Gazzillo et al, 2015 ; Tanzilli, Lingiardi, & Hilsenroth, 2018 ), and to study countertransference with patients with eating disorder (Satir, Thompson-Brenner, Boisseau, & Crisafulli, 2009 ; Colli et al, 2015 ) and suicidal behavior (Yaseen et al, 2013 ). Monitoring countertransference also has potentials as a feedback instrument for the therapist, and to capture negative or harmful reactions in the mind of the therapist, as for example reactions connected to burnout or compassion fatigue ( e.g.…”
Section: Introductionmentioning
confidence: 99%